Pemaknaan Tanah Eks Swapraja (Kerajaan) sebagai Tanah Adat di Kota Surakarta - Dewi, IGA Gangga Santi; APHA, Journal Manager (Jurnal Hukum Adat Indonesia, 2018)
The meaning former kingdom lands which is diffrent between the government and the kingdom became one of the triggers of the conflict in Indonesia. Horizontal conflict involves the community, kingdom and local government. Likewise at this time there were many conflicts related to ex-kingdom land which eventually ended in a court dispute in Surakarta City, namely the domein land of the Surakarta Palace and the domein Mangkunegaran land. The research was carried out using the Socio Legal method qualitatively. It was hoped that the meanings hidden behind the object and the subject under study were found. This approach was carried out to understand the law in the context of the community. In this study look at the reality of the validity of the land of the former Kingdom in Surakarta. The reality of the absence of a Government Regulation as instructed in Dictum IV letter B of UUPA resulted in a prolonged conflict between the Regional Government and the heirs of the kingdom as well as the people who have an interest in the land of the former kingdom. Based on the results of the study, the Kingdom of Surakarta, namely the Keraton and Mangkunegaran are indigenous people, because the King as the customary leader still has the same territorial area and descent and has authority in and out of his customary area. So that the land of the former kingdom applies as customary land for the Kingdom of Surakarta.